2019
DOI: 10.1038/s41598-019-51449-6
|View full text |Cite
|
Sign up to set email alerts
|

Ageing deformation of tailings dams in seasonally frozen soil areas under freeze-thaw cycles

Abstract: The freeze-thaw cycle is one of the important factors in inducing a dam-break in the permafrost region, so it is of great practical significance to study the mechanism of the failure deformation of tailings dams under freeze-thaw cycles. In this paper, the water-heat-force coupling model of a tailings dam considering frost-thaw damage is established, and the freeze-thaw cyclic ageing deformation of a tailings dam in a seasonally frozen soil area is studied. The correctness of the model is validated by numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Thus in the tropical zone, the frequency and intensity of rainfall may directly affect the transport infrastructure and indirectly affect commercial and residential buildings due to the rainfall-induced landslides near cities. Cracks in roads and damage to tailings dams have been observed in the polar zones due to the snow and seasonally frozen soil (Jin et al, 2019).…”
Section: Climate Change and Land Use Impacts On The Artificial Systemsmentioning
confidence: 99%
“…Thus in the tropical zone, the frequency and intensity of rainfall may directly affect the transport infrastructure and indirectly affect commercial and residential buildings due to the rainfall-induced landslides near cities. Cracks in roads and damage to tailings dams have been observed in the polar zones due to the snow and seasonally frozen soil (Jin et al, 2019).…”
Section: Climate Change and Land Use Impacts On The Artificial Systemsmentioning
confidence: 99%
“…Scholars at home and abroad have contributed certain research results regarding the mechanical properties and deterioration characteristics of geotechnical materials 11 15 ; many found that soil sites are vulnerable to erosion by the natural environment, and a large number of cracks generally develop on the surface, where dry shrinkage and freeze-thaw are common influencing factors 16 , 17 . Much of the current research has focused on the macro-microscopic changes in the development of fractures in soil samples under dry shrinkage and freeze-thaw conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers [6][7][8][9] have investigated the effect of freeze-thaw cycles on the mechanical properties of tailings through a vast number of experimental and theoretical studies. Yang proposed stress-strain curves for seasonal and permafrost soils for various influencing parameters using indoor uniaxial compression tests.…”
Section: Introductionmentioning
confidence: 99%